Flying Friars and Other Exceptions - Grosso, Michael (Journal of Scientific Exploration, 2020)
Stephen Braude’s editorial “Does Telepathy Threaten Mental Privacy” speaks to one reason some people might resist accepting the reality of paranormal abilities. It is somewhat of a puzzle why so many otherwise rational people shy away from psi. If we accept telepathy, it might seem we’re exposed to others snooping on our innermost secrets and intentions. Deploying a distinction made by C. D. Broad between telepathic cognition and telepathic interaction, Braude argues that our fear of telepathic intrusion is greatly exaggerated. I, for example, often think of someone just before he or she calls on the phone. When that happens, I have no knowledge of what the caller is going to tell me, No cognition, just a bit of interaction. Telepathic connection doesn’t necessarily imply telepathic cognition. No danger of your hidden self being exposed in most common forms of telepathy. There are, however, some examples where it looks like real telepathic cognition comes into play. In the early stages of 17th century Joseph of Copertino’s career as a priest, his superiors had to ask Joseph to desist from calling the brothers out in public for every peccadillo they committed. In a typical example cited, he embarrassed a brother for thinking about eating cherries and other things while saying his prayers. His superiors urged Joseph to be more discreet and say things like—“you need to adjust your moral compass.” Joseph did learn to be more discreet but his Vita shows him repeatedly tuning into the specifics of other minds. For example, he was able to distinguish persons who came merely to observe him out of curiosity. Let me quote one sworn deposition from a Brother Francesco that illustrates telepathic cognition.